Enhancement of Electrochemical Stability about Silicon/Carbon Composite Anode Materials for Lithium Ion Batteries. (1st October 2015) - Xiao, Wei; Miao, Chang; Yan, Xuemin; Sun, Qing; Mei, Ping
Abstract : Silicon/carbon (Si/C) composite anode materials are successfully synthesized by mechanical ball milling followed by pyrolysis method. The structure and morphology of the composite are characterized by X-ray diffraction and scanning electron microscopy and transmission electron microscope, respectively. The results show that the composite is composed of Si, flake graphite, and phenolic resin-pyrolyzed carbon, and Si and flake graphite are enwrapped by phenolic resin-pyrolyzed carbon, which can provide not only a good buffering matrix but also a conductive network. The Si/C composite also shows good electrochemical stability, in which the composite anode material exhibits a high initial charge capacity of 805.3 mAh g −1 at 100 mA g −1 and it can still deliver a high charge capacity of 791.7 mAh g −1 when the current density increases to 500 mA g −1 . The results indicate that it could be used as a promising anode material for lithium ion batteries.